2012
DOI: 10.1021/nn303795r
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Electrolyte Background for Biochemical Sensing with Ion-Sensitive Field-Effect Transistors

Abstract: Silicon nanowire field-effect transistors have attracted substantial interest for various biochemical sensing applications, yet there remains uncertainty concerning their response to changes in the supporting electrolyte concentration. In this study, we use silicon nanowires coated with highly pH-sensitive hafnium oxide (HfO(2)) and aluminum oxide (Al(2)O(3)) to determine their response to variations in KCl concentration at several constant pH values. We observe a nonlinear sensor response as a function of ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 47 publications
8
106
1
Order By: Relevance
“…This conversion is similar to previous work. [29,41] We find that a point of zero charge between 6 and 7 gives a good fit with the data. We We conclude this discussion with Figure 3c, showing the calculated surface potential versus the activity of calcium ions a Ca 2+ and pH for the parameters obtained above.…”
Section: Resultsmentioning
confidence: 63%
“…This conversion is similar to previous work. [29,41] We find that a point of zero charge between 6 and 7 gives a good fit with the data. We We conclude this discussion with Figure 3c, showing the calculated surface potential versus the activity of calcium ions a Ca 2+ and pH for the parameters obtained above.…”
Section: Resultsmentioning
confidence: 63%
“…For example, the FET-sensor of Tarasov et al showed a shift in threshold voltage of 59 mV for every 10-fold increase in KCl concentration. 96 They attributed this effect to pH independent selective adsorption of anions. Similarly, a non-linear FET-sensor response to increasing NaCl concentration was measured by Maekawa et al 97 This empirical observation has also been observed in molecular dynamics simulation studies.…”
Section: Buffer Solutionmentioning
confidence: 99%
“…Taking into account the electrochemical phenomenon occurring at the interface, the relationship between the surface potential and pH are demonstrated as following: ψ0=2.3kTq(pHpzcpH)(ββ+1)and the sensitivity is defined by: S=ψ0(pHpzcpH)=2.3kTq(ββ+1)Where S is the pH sensitivity, pH pzc is the pH of the point of zero charge, and β is a parameter depending on the material properties such as the constants of dissociation and the number of reactive available sites 126,127 at the surface of electronic material as well as the electrolyte composition 128,129 affecting the double layer capacitance C d .…”
Section: Transduction Mechanisms At the Analyte Medium-device Intementioning
confidence: 99%